Correction:Decreased Thymic Output Contributes to Immune Defects in Septic Patients(J. Clin. Med. (2020), 9, (2695), 10.3390/jcm9092695) - Sommer, Natascha; Noack, Steffen; Hecker, Andreas; Hackstein, Holger; Bein, Gregor; Weissmann, Norbert; Seeger, Werner; Mayer, Konstantin; Hecker, Matthias (Journal of Clinical Medicine, 2022)
In the original article, there were errors in Figure 1D (panel CD8-Control). Changes are below. The authors apologize for any inconvenience caused and state that the scientific conclusions are unaffected. The original article has been updated.
CRIS-Team Scopus Importer:2022-09-30